Biogenic volatile organic compounds in the grapevine response to pathogens, beneficial microorganisms, resistance inducers, and abiotic factors. (19th August 2021) - Lazazzara, Valentina; Avesani, Sara; Robatscher, Peter; Oberhuber, Michael; Pertot, Ilaria; Schuhmacher, Rainer; Perazzolli, Michele
Abstract : Grapevine responses to phytopathogens, beneficial microorganisms, resistance inducers, and abiotic factors involve the production of volatile organic compounds with antimicrobial, antioxidant, and signaling roles. Abstract: The synthesis of volatile organic compounds (VOCs) in plants is triggered in response to external stimuli, and these compounds can migrate to distal tissues and neighbouring receivers. Although grapevine VOCs responsible for wine aroma and plant–insect communications are well characterized, functional properties of VOCs produced in response to phytopathogens, beneficial microorganisms, resistance inducers, and abiotic factors have been less studied. In this review, we focused on the emission patterns and potential biological functions of VOCs produced by grapevines in response to stimuli. Specific grapevine VOCs are emitted in response to the exogenous stimulus, suggesting their precise involvement in plant defence response. VOCs with inhibitory activities against pathogens and responsible for plant resistance induction are reported, and some of them can also be used as biomarkers of grapevine resistance. Likewise, VOCs produced in response to beneficial microorganisms and environmental factors are possible mediators of grapevine–microbe communications and abiotic stress tolerance. Although further functional studies may improve our knowledge, the existing literature suggests that VOCs have an underestimated potential application as pathogen inhibitors, resistance inducers against biotic or abiotic stresses, signalling molecules, membrane stabilizers, and modulators of reactive oxygen species. VOC patterns could also be used to screen for resistant traits or to monitor the plant physiological status.